Code-Switching di Pembelajaran Bahasa Inggris: Solusi atau Hambatan Imersi? - Bilqis, Sang Maharah (Journal of Information Systems and Management (JISMA), 2025)
The purpose of this study is to analyze the use of code-switching in English language instruction in Indonesian high schools, with an emphasis on the benefits and challenges that arise in the language immersion process in English learning. Through descriptive qualitative research, data is collected through student observation, reflective analysis, and informal student interviews. The results indicate that the strategic use of code-switching by teachers can increase students' comprehension of the material, decrease their level of understanding, and increase their sensitivity, especially for those who have a lower proficiency in English. However, more advanced usage can cause a dependence on the first language, which hinders the immersion learning process. Factors such as the use of English in daily interactions can negatively impact students' perceptions and responses to this strategy. Accordingly, code-switching can be an effective educational solution if it is used carefully and according to students' needs, as well as enhancing the concept of differentiation in instruction in the Merdeka curriculum.